Zinc-Induced Metallothionein in Centenarian Offspring From a Large European Population: The MARK-AGE Project. (17th October 2017) - Giacconi, Robertina; Costarelli, Laura; Piacenza, Francesco; Basso, Andrea; Bürkle, Alexander; Moreno-Villanueva, Maria; Grune, Tilman; Weber, Daniela; Stuetz, Wolfgang; Gonos, Efstathios S; Schön, Christiane; Grubeck-Loebenstein, Beatrix; et al.
Abstract: Metallothionein (MT) family are cysteine-rich proteins that regulate zinc (Zn) homeostasis and protect against oxidative damage. Studies in transgenic mice have shown that MT favorably influence longevity, although their role in human aging is not completely understood. Within the European multicenter study MARK-AGE, we analyzed MT induction after Zn treatment in peripheral blood mononuclear cells (PBMCs) and its relation with redox biomarkers in 2, 936 age-stratified subjects (35–75 years) including the general population (RASIG), centenarian offspring (GO), and their spouses (SGO). We found that the lymphocyte capability to induce MT in response to Zn is not affected by aging. However, GO participants showed lower Zn-induced MT and increased basal expression of MT1A, MT1X, and ZnT-1 genes than RASIG subjects. Moreover, Zn-induced MT levels were found to be inversely related with oxidative stress markers (plasma protein carbonyls, 3-nitrotyrosine, and malondialdehyde) in the whole population, but not in GO subjects. In conclusion, our results support the hypothesis that the response to Zn is attenuated in PBMCs of centenarian offspring compared to the general population as a consequence of a tighter control of Zn homeostasis which is likely to provide them constant protection against stress stimuli over the whole lifespan.